РЕТРОСПЕКТИВА ТА СУЧАСНИЙ ЗМІСТ ПАРИТЕТНОЇ ДЕМОКРАТІЇ: ТЕОРЕТИКО-ПРАВОВИЙ АСПЕКТ - Грицай, Ірина Олегівна (SUPREMANCE OF LAW, 2017)
This article explores the historical development of the phenomenon of parity democracy. It gives a theoretical and legal description of the nature and content of the concepts of «parity democracy» and «gender democracy». Scientific approaches to the relationship between parity and gender democracy are systematized. We propose to view them as interrelated and interdefinable phenomena. We emphasise that the overall objective of parity and gender democracy is the establishment of social justice.
Keywords: parity democracy; gender democracy; civil society; equality of rights and freedoms of man and citizen; gender balance